Collisional angular momentum depolarization of OH(A) and NO(A) by Ar: a comparison of mechanisms. - Brouard, M; Chadwick, H; Chang, Y; Eyles, C; Aoiz, F; Kłos, J (2011)
This paper discusses the contrasting mechanisms of collisional angular momentum depolarization of OH(A(2)Σ(+)) and NO(A(2)Σ(+)) by Ar. New experimental results are presented for the collisional depolarization of OH(A) + Ar under both thermal and superthermal collision conditions, including cross sections for loss of both angular momentum orientation and alignment. Previous work on the two systems is summarized. It is shown that NO(A) + Ar depolarization is dominated by impulsive events in which the projection of the angular momentum, j, along the kinematic apse, a, is nearly conserved, and in which the majority of the trajectories can be described as "nearside." By contrast, at the relatively low collision energies sampled at 300 K, OH(A) + Ar depolarization is dominated by attractive collisions, which show a preponderance of "farside" trajectories. There is also evidence for very long-lived, complex type trajectories in which OH(A) and Ar orbit each other for several rotational periods prior to separation. Nevertheless, there is still a clear preference for conservation of the projection of j along the kinematic apse for both elastic and inelastic collisions. Experimental and theoretical results reveal that, as the collision energy is raised, the depolarization of OH(A) by Ar becomes more impulsive-like in nature.